Síntese de derivados de γ-lactamas, Δ1-pirrolinas e pirróis a partir de chalconas empregando aziridinas e 2H-azirinas - Martelli, Lorena Suelen Ribeiro (Universidade Federal de São Carlos, 2024)
The search for efficient synthetic methods for 5-membered N-heterocycles, such as γ-lactams and pyrroles, is constantly necessary, as these scaffolds are widely found in natural products and synthetic compounds with biological activities. In this aspect, we developed a simple, efficient and diastereoselective synthesis of new γ-lactams from aziridines, based on a previous reported method by our research group for the synthesis of γ-lactones, employing the Horner–Wadsworth–Emmons reaction. We optimized the time, concentration, solvent and the stoichiometric proportion of substrates, and the best reaction condition was stablished using NaH as base in THF at 17 oC for 15 h. We then investigated the scope and limitations of the developed protocol. In total, 15 examples were obtained in 14-88% yield and two limitations observed regarding the presence of the NO2 group and the protected aziridine. Furthermore, it was possible to scale-up the reaction in 10-fold and also initiate the enantioselective version using a chiral organocatalyst. Next, we investigated the synthesis of Δ1-pyrrolines from chalcones and 2H-azirines via photoredox catalysis induced by visible light, under continuous flow regime. Different photocatalysts, solvents, residence time, reactors, concentration, catalyst loading and stoichiometry were tested. The best condition was achieved using blue LED, 7 mol% mesitylacridinium as catalyst in DCE as solvent, which resulted in a Δ1-pyrroline ring with 82% yield and 73:27 diastereoisomeric ratio. After established the best reaction condition, we carried out the investigation of the reaction scope and its limitations. However, the major diastereoisomers of the synthesized derivatives showed low stability in solvents such as chloroform, dimethyl sulfoxide and acetone, which did not allow the efficient characterization of the compounds by NMR. The Δ1-pyrrolines and its pyrrole derivatives showed IC50 between 1.03 and 8.0 µM, in preliminary tests against the protozoan Plasmodium falciparum, in addition, did not show cytotoxicity against HepG2 cells. Thus, the Δ1-pyrrolines were oxidized with DDQ affording seven pyrroline derivatives in 12-47% yield over two steps. The products were sent to be tested against P. falciparum.
Synthesis of γ-lactam, Δ1-pyrroline and pyrrole derivatives from chalcones using aziridines and 2H-azirines
Keywords: Lactamas; Fotocatálise; Fluxo contínuo; Lactams; Photocatalysis; Continuous flow; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA